(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Samad Nagar pond situated in Jatrabari, Dhaka showed mean air temperature 20 - 30 °C and water temperature 19 - 28°C. Secchi depth (Zs) varied from 28.67 - 44.5 cm and pH 6.6 - 8.8. The mean DO and alkalinity ranged 5.34 - 10.00 mg/1 and 0.58 - 1.08 meq/1, respectively. Free C02, SRP and SRS ranged 1.31 - 4.21 mg/1, 158.39 - 635.70 pg/1 and 13.32 - 28.65 mg/I, respectively. During the study period, seasonal mean values of transparency was higher in monsoon and lower in winter. pH, alkalinity remained higher in winter but lower in monsoon. From aquatic plant communities of the pond, phytoplankton represented by 33 species of which 54.55% belonged to Chlorophyceae (54.55%) followed by Bacillariophyceae (13.64%), Cyanophyceae (13.64%), Euglenophyceae (13.64%) and Dinophyceae (4.55%). The population density of phytoplankton community ranged 6.16 - 25.96><1 06 ind/1. Benthic diatom density varied from 2.64- 11 .00 x 1 06 ind/1. Benthic diatom population was the highest (I lxlO6 ind/1) in late October and lowest in early September (2.64 xio6 ind/1). Chi a and phaeophytin concentration varied 5.10 - 228.51 pg/1 and 2.05 - 1513.36 pg/1, respectively. Aquatic macrophyte communities were represented by 23 species where Eichhornia crassipes (Mart.) Solms. , Ipomoea aquatica Forsk, Ipomoea fistulosa Mart., Telanthera philoxeroides Moq., Rumex maritimus L., Eclipta prostata (L.) L. and Salvinia natans L. were observed all over the study period. Asiat. Soc. Bangladesh, Sci. 41(2): 253-262, December 2015